Identifikasi Kelimpahan Mikroplastik Sungai Batanghari Wilayah Nipah Panjang Kabupaten Tanjung Jabung Timur - Siti Umi Kalsum; Hadrah Hadrah; Anggrika Riyanti; Andi Irfan Maulana (Universitas Batanghari Jambi, 2023)
One of the biggest environmental issues today is plastic waste. This waste cannot be avoided and continues to increase which in its decomposition takes 50-100 years and will be fragmented into smaller forms called microplastics. Microplastic measuring < 5 mm with various shapes. The people of the Nipah Panjang area dispose of plastic waste into the Batanghari River which is likely to cause microplastic content. To determine the number of microplastics, it is necessary to identify the abundance of microplastics found in the Nipah Panjang area on the Batanghari River using quantitative methods. The tool used is Planktonet mesh 150 with a diameter of 20 cm. The sampling process was carried out for one day with two samplings, namely in the morning at low tide at 09.00-11.00 WIB and in the afternoon at high tide at 15.00 WIB. The study's results were sampling in the morning at low tide with 327 microplastic particles and the highest in the afternoon at high tide, namely 443 microplastic particles. The temperature in the morning and evening ranges from 29°C - 32°C. The results showed that four types of microplastics were found, namely the type of fiber, filament, fragment, and granule. From the four locations of Sungai Air samples, the most microplastic fragments were found with a total of 353 particles, the second most were filament types with a capacity of 191 particles, the third type of fiber with a total of 186 particles, and the least types of granules with a total of 40 particles. Microplastic at low tide is lower than at high tide. The abundance of microplastics from the four sampling locations of river water is 25,666.67 particles/m3.